d Determinan Pertumbuhan Pembiayaan UMKM pada Bank Umum Syariah dengan Moderasi Non Performing Financing : Bank Umum Syariah - Feni Marlia; Jaka Waskito; Amirah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of BI Rate, Third-Party Funds (DPK), Inflation, and Financing to Deposit Ratio (FDR) on MSME financing growth, with Non-Performing Financing (NPF) as a moderating variable in Islamic Commercial Banks in Indonesia during 2021–2025. Using secondary data from the Financial Services Authority (OJK), 54 observations were analyzed through Multiple Linear Regression and Moderated Regression Analysis (MRA). The results show that BI Rate negatively affects MSME financing growth, while DPK and FDR have positive effects. Inflation has no significant effect. NPF moderates only the relationship between FDR and MSME financing growth, providing insights for improving Islamic banking financing strategies. Keywords: BI Rate; Third Party Funds; Inflation; Financing to Deposit Ratio; Non-Performing Financing